The contribution of laboratory animals to diagnostic imaging research in Greece - TSELEPIDIS, S.; VASSIOU, K.; ARVANITIS, D.; KALOGEROPOULOU, C.; MARINOU, K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Biomedical research in Greece has rapidly developed during the last 30 years. Diagnostic imaging groundwork is a significant field of interest which has been developed by taking advantage of the basic and applied research capacities including the use of small and large animal models, conventional and/or genetically modified ones. This important outbreak in research has been enhanced by the construction of modern facilities in universities, medical and other academic research centers, the use of new advanced installed equipment, modern imaging techniques, specific contrast media and, of course, specialized personnel. In this manuscript, the research performed regarding diagnostic imaging techniques using animal models in Greece since 1983 is presented. More specifically a recording of the Greek research centers, the number of researchers, species and figures of animal models, diagnostic imaging techniques used, as well as the contribution of projects in the evolution of diagnostic imaging in medicine and veterinary science is presented.